Change of signs, symptoms and voice quality evaluations throughout a 3‐ to 6‐month empirical treatment for laryngopharyngeal reflux disease. (5th June 2018) - Lechien, J.R.; Finck, C.; Khalife, M.; Huet, K.; Delvaux, V.; Picalugga, M.; Harmegnies, B.; Saussez, S.
Abstract : Objective: To assess the usefulness of voice quality measurements as a treatment outcome in patients with laryngopharyngeal reflux (LPR)‐related symptoms. Design: Prospective uncontrolled multi‐centre study. Material and methods: A total of 80 clinically diagnosed LPR patients with a reflux finding score (RFS)>7 and a reflux symptom index (RSI)>13 were treated with pantoprazole and diet recommendations during 3 or 6 months, according to their evolution. RSI; RFS; blinded Grade, Roughness, Breathiness, Asthenia, Strain and Instability (GRBASI) and aerodynamic and acoustic measurements were evaluated at baseline, 3 months (n = 80), and 6 months (n = 41) post‐treatment. We conducted a correlation analysis between the adherence to the diet, and the evolution of both signs and symptoms and between videolaryngostroboscopic signs and acoustic measurements. Results: Reflux symptom index, RFS, perceptual voice quality evaluations (dysphonia, roughness, strain and instability), and aerodynamic and acoustic measurements (ie, percent jitter and percent shimmer) were significantly improved at 3 months post‐treatment but not at 6 months. Percent jitter was the most useful outcome for evaluating the clinical evolution of patients throughout the treatment course. A significant relationship between globus sensation and posterior commissure hypertrophy was documented; both seemed to significantly improve from 3 to 6 months. The correlation analysis revealed correlations between adherence to diet recommendations and the improvement of symptoms and between posterior commissure granulation severity and acoustic measurement impairments. Conclusion: Voice quality improved in a manner similar to both signs and symptoms throughout a 6‐month empirical treatment with better improvement the 3 first months. Voice quality assessments can be used as indicators of treatment effectiveness in patients with LPR‐related symptoms.